Non-thermal radiation from a runaway early-type star - del Valle, Maria Victoria (2012)
HD 195592 is an O-type supergiant star, known as a well-established runaway. Recently, a Fermi γ-ray source (2FGL J2030.7+4417) with a position compatible with that of HD 195592 has been reported. Our goal is to explore a scenario where HD 195592 is the counterpart of the Fermi γ-ray source. The high-energy emission would be inverse Compton radiation produced in the bowshock of the runaway star. We calculate relativistic particle energy losses and the resulting radiation from the bowshock of HD 195592 and show that the latter is compatible with the detected γ-ray emission. We conclude that the Fermi source 2FGL J2030.7+4417 might be produced, under some energetic assumptions, by inverse Compton up-scattering of infrared photons from locally heated dust. HD 195592 might therefore be the very first object detected belonging to the category of γ-ray emitting runaway massive stars, whose existence has been recently predicted.